2020
DOI: 10.1158/0008-5472.can-19-3281
|View full text |Cite
|
Sign up to set email alerts
|

p38γ MAPK Is Essential for Aerobic Glycolysis and Pancreatic Tumorigenesis

Abstract: ◥KRAS is mutated in most pancreatic ductal adenocarcinomas (PDAC) and yet remains undruggable. Here, we report that p38g MAPK, which promotes PDAC tumorigenesis by linking KRAS signaling and aerobic glycolysis (also called the Warburg effect), is a novel therapeutic target. p38g interacted with a glycolytic activator PFKFB3 that was dependent on mutated KRAS. KRAS transformation and overexpression of p38g increased expression of PFKFB3 and glucose transporter GLUT2, conversely, silencing mutant KRAS, and p38g … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 48 publications
2
65
0
Order By: Relevance
“…Recently, Liberti et al revealed that heptelidic acid exerted anti-tumor effects in cells that depended on the Warburg effect (WE) 30 . Likewise, p38 MAPK signaling is known to be a key regulatory signaling pathway of glycolysis 31 33 in pancreatic cancer cells and our findings showed that heptelidic acid exerted an anti-tumor effect which was mediated by p38 signal transduction. These findings suggest that anticancer therapy, especially pancreatic cancer treatment, utilizing heptelidic acid may prove effective.…”
Section: Discussionsupporting
confidence: 59%
“…Recently, Liberti et al revealed that heptelidic acid exerted anti-tumor effects in cells that depended on the Warburg effect (WE) 30 . Likewise, p38 MAPK signaling is known to be a key regulatory signaling pathway of glycolysis 31 33 in pancreatic cancer cells and our findings showed that heptelidic acid exerted an anti-tumor effect which was mediated by p38 signal transduction. These findings suggest that anticancer therapy, especially pancreatic cancer treatment, utilizing heptelidic acid may prove effective.…”
Section: Discussionsupporting
confidence: 59%
“…Moreover, most of the previous studies focused on the role of a certain gene in PDAC, and most of them studied the effect of genes on the function of PDAC cells, for example: Yang et al (2020) found that chlorogenic acid can inhibit cell bioenergy by regulating the c-Myc-TFR1 axis, thereby inhibiting pancreatic cancer. The study by Wang et al (2020) shows that p38γ links KRAS oncogene signal transduction and Warburg effect through PFBBF3 and Glut2 to promote the occurrence of pancreatic cancer. But our study creatively studied the relationship between glycolysis-related genes (GRGs) and the clinical risk of PDAC patients, and the constructed model can predict the prognosis of PDAC patients well.…”
Section: Discussionmentioning
confidence: 99%
“…Aerobic glycolysis is essential for cancer cells growth and invasion 22‐24 . In PDAC, recent studies reported that aerobic glycolysis of metabolic reprogramming promoted pancreatic tumorigenesis, proliferation and metastasis 8,25‐27 . Although there are many studies on the relationship between PDAC and glycolysis, researches which involve biomarkers and prognosis of patients with PDAC relating to glycolysis are seldomly reported.…”
Section: Discussionmentioning
confidence: 99%
“…A high rate of aerobic glycolysis, known as the Warburg effect, is a hallmark of cancer cell glucose metabolism 7 . Recent studies reported that aerobic glycolysis is active in PDAC in promoting pancreatic tumorigenesis, proliferation and invasion 8‐10 . Furthermore, pyruvate kinase M2, which promotes cell survival and invasion under metabolic stress by enhancing the Warburg effect in PDAC, 11 promotes PDAC invasion and metastasis through phosphorylation and stabilization of PAK2 protein 12 .…”
Section: Introductionmentioning
confidence: 99%